Pengaruh Social Media Marketing, Perceived Price, dan Brand Image Terhadap Purchase Intention pada Generasi – Z di KOPILOJIK - Rafilino Rianda Sastrodiningrat; Ryna Parlyna; Inkreswari Retno Hardini (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to analyze the influence of social media marketing, perceived price, and brand image on Generation Z’s purchase intention toward KOPILOJIK. This phenomenon has emerged alongside the growth of digital marketing and social commerce, where platforms such as Instagram, TikTok, and other social media have become the primary channels for KOPILOJIK to build brand exposure, convey promotional information, and shape price perceptions and brand image among young consumers. This research uses a quantitative approach with a survey method. The study population consists of Generation Z in Jakarta who are familiar with KOPILOJIK and have either visited or made a purchase at KOPILOJIK or follow KOPILOJIK’s social media accounts. The sampling technique used is purposive sampling with a minimum of 140 respondents. Data collection was conducted via an online questionnaire using Google Forms, consisting of four research variables measured using a Likert scale. The data obtained were analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The results indicate that social media marketing, perceived price, and brand image have a positive and significant effect on Generation Z’s purchase intention toward KOPILOJIK. This research is expected to provide a theoretical contribution to the development of consumer behavior studies in the context of digital marketing for cafes.